Interpreters and wardens. Education and social role of Yaquim women - Anita Gramigna (University of Bologna, 2017)
This work lies within a field research that began in 2014 among the Yaqui tribe of the Mexican state of Sonora (Gramigna & Rosa, 2016) and that continued, in the following years, with the collection of further evidences. The goal is to identify the specificity of the educational and social role the Yaquim women play in their community. To this end, we tried to explore their everyday life, to grasp, in the fabric of real life, the salient signs of a symbolic world of great formative significance.The epistemological framework refers to an interpretative pedagogy and thus to a hermeneutical approach. The inquiry methodology, of qualitative kind, is intended as a normative epistemology and implies a systemic perspective.The people involved were informed of the purposes of our conversation and have committed themselves to cooperate in a common project of valorisation and divulgation of the yaqui culture, therefore they have not asked nor received any compensation.